The Moral Economy Reconsidered Russia’s Search For Agrarian Capitalism - Wegren, S. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
Sure to be controversial and spur debate, this book presents a powerful analysis of rural change to marketization and globalization. Using Russia as a case study, it examines the how the rural population responded to reform policies during the transition away from communism. Wegren draws upon extensive field work, survey data, interviews, and wide-ranging Russian language source material to investigate adaptive behaviours by different groups of the rural population. The differentiated and nuanced analysis sheds considerable light on debates over whether actors are motivated mainly by rational or moral considerations.